Como os professores trabalharam a literatura infantil na pré-escola entre os anos de 2016 a 2023? - Rocha, Juliana Rodrigues da (Brasil, 2024)
This research originated in 2023 during the Children's Literature course, part of the Pedagogy program at the Universidade Federal do Amazonas – UFAM. The study aimed to understand how dissertations and theses published between 2016 and 2023 reveal the pedagogical practices of preschool teachers, contributing to reflections and recommendations for these practices and recognizing the concepts of children's literature that influence teaching practices. These practices serve as a significant resource in the teaching-learning process. The research adopted a qualitative methodology based on bibliographic research with a descriptive approach, analyzing articles from the past eight years collected from Google Scholar, SciELO, CAPES, and the repositories of UFAM and UEA. Based on studies from these sources, it is evident that children's literature is relevant in preschool education as a collaborative pedagogical practice that fosters learning development in the school environment.